Early resumption of sex after voluntary medical male circumcision for HIV prevention within a programmatic delivery setting in Botswana. (November 2019) - Pintye, Jillian; Wirth, Kathleen E; Ntsuape, Conrad; Kleinman, Nora J; Spees, Lisa P; Semo, Bazghina-Werq; Mawandia, Shreshth; Ledikwe, Jenny H
To maximize the public health benefits of voluntary medical male circumcision (VMMC) in real-world settings, sexual abstinence is recommended for six weeks following VMMC to ensure complete wound healing. We determined the frequency and predictors of early resumption of sex among a cohort of HIV-negative, sexually active men 18–49 years who underwent VMMC within a public-sector clinic in Botswana. Multivariate robust Poisson regression methods were used to identify predictors of having any sexual intercourse in the last six weeks since undergoing VMMC. In total, 433/519 (83%) men had data available on sexual activity at six weeks post-VMMC. Median age was 27 years, 57% had a higher than secondary education, 72% were employed, and 9% were married. Overall, 122/433 (28%) men had sexual intercourse within the six weeks since VMMC, of whom 36% reported inconsistent condom use. Compared to men ≥34 years, men aged <30 years (adjusted risk ratio [aRR] = 1.71, 95% CI 0.95–3.08) and men 30–34 years had a two-fold higher likelihood of resuming sexual activity early in multivariate analyses (aRR = 2.31, 95% CI 1.26–4.25, Wald p = 0.018). Employed men were more likely to resume sexual activity early than unemployed men (aRR = 1.58, 95% CI 1.02–2.44, p = 0.039). Additional interventions are needed to encourage abstinence until complete wound healing.